Implementation of anti-collision train prototype based on arduino microcontroller - Ahmed R. Ibrahim; Ziad M. Abood (International Journal of Advances in Applied Sciences, 2020)
Because the electrical train become a popular mode and Eco-Friendly of transport in largest cities in the world in our day life and due to increase in the train accidents.  In this paper a train collision avoidance system is designed and implemented using Arduino NANO and an ultrasonic sensor. A prototype is used to explain the system function using; two train samples on single track. The ultrasonic sensor is connected to the Arduino NANO to transmit the measured distance to the microcontroller and make the decision to stop the train. The ultrasonic sensor on both trains from the front end and continually measures the distance between them and when they reach the decided distance a signal to the trains engines will slow down or stop both trains to avoid a collision while when the ultrasonic sensors from the rear-end continually measure the distance between them and when it reaches the decided distance a signal to the train engine will slow down and stop the first train to avoid a collision.